2006
DOI: 10.1128/mcb.26.6.2160-2174.2006
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Rac1 in Activation of Multicomponent Nox1- and Nox3-Based NADPH Oxidases

Abstract: Reactive oxygen species (ROS) are produced in phagocytic cells by NADPH oxidase, a complex that transports electrons across membranes and generates superoxide anion from molecular oxygen. This enzyme is assembled from a membranespanning flavocytochrome b 558 , composed of Nox2 (also called gp91 phox ) and p22 phox and four cytosolic factors (p47 phox

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
220
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 209 publications
(236 citation statements)
references
References 60 publications
16
220
0
Order By: Relevance
“…Noxa1 was designated as a "Nox activator" based on its homology to p67 phox , which binds to Rac1 or Rac2 and plays a more direct role in modulating oxidase activity. Recent evidence suggests that Rac1 also regulates Nox1 most likely through GTP-dependent interactions with the Nox activator, Noxa1 [16][17][18][19] We showed that the association of Noxa1 with the plasma membrane depends on its interaction with Noxo1 [17]. These structural and functional similarities between the Nox and phox regulators may explain why Noxo1 and Noxa1 can function in partially compensating for p47 phox and p67 phox in supporting Nox2 activity [8,[13][14][15].…”
Section: Introductionmentioning
confidence: 60%
See 4 more Smart Citations
“…Noxa1 was designated as a "Nox activator" based on its homology to p67 phox , which binds to Rac1 or Rac2 and plays a more direct role in modulating oxidase activity. Recent evidence suggests that Rac1 also regulates Nox1 most likely through GTP-dependent interactions with the Nox activator, Noxa1 [16][17][18][19] We showed that the association of Noxa1 with the plasma membrane depends on its interaction with Noxo1 [17]. These structural and functional similarities between the Nox and phox regulators may explain why Noxo1 and Noxa1 can function in partially compensating for p47 phox and p67 phox in supporting Nox2 activity [8,[13][14][15].…”
Section: Introductionmentioning
confidence: 60%
“…The pcDNA3.1 plasmids (Invitrogen) containing the complete coding sequence of human Nox1, p41 nox (Noxo1α and Noxo1β), p51 nox (Noxa1), and p22 phox were described previously [5,8,17]. Human Noxo1γ in pcDNA3.1 and Noxo1δ in pcDNA3.1were made from Noxo1β and Noxo1α using the QuickChange II XL Site-Directed Mutagenesis Kit (Stratagene), respectively.…”
Section: Construction Of Plasmidsmentioning
confidence: 99%
See 3 more Smart Citations